Modern or medieval? Analysis of an iron anchor from Camuscross, Scotland and direct dating methods for metal artefacts. (June 2019) - Claggett, Daniel; McCarthy, John; Murray, William; Sebo, Erin; Jouttijärvi, Arne; Hüls, Matthias; Benjamin, Jonathan
Abstract: In 2009, an iron anchor was found by the coast of Camuscross, Isle of Skye, Scotland after the digging of a drainage channel exposed the object. There was initial speculation in media coverage that the anchor might be Viking, perhaps dating between the 9th–12th centuries CE. However, due to its damaged condition and the lack of precise stratigraphic context, determining the age of the anchor has been challenging. This article will discuss a subsequent program of investigation to date the anchor, including metallurgical and radiometric analysis, and will present a number of possible interpretations based on this analysis. It will also consider the broader context and implications of using the two analytical methods of absolute dating applied to the anchor and how they can help to improve interpretation of archaeological materials. Highlights: A potentially Viking anchor was found in Camuscross, Isle of Skye in 2009. It has since been housed at a museum on Skye. A suite of multi-disciplinary analyses was undertaken to determine the age and origin of the artefact. These analyses have allowed for a reliable date range and provenance for the artefact to be established.